Pengujian Performance Adsorben Serat Buah Mahkota Dewa (Phaleria Marcocarpa (Scheff)) Dan Clay Terhadap Larutan Yang Mengandung Logam Kromium - Sri Haryati (Journal of Applied and Engineering Chemistry, 2011)
The adsorption method is very promising in the treatment of the industrial effluent containing hazardous metals because it provides a high absorption capacity. This study aims to separate the chromium ions from artificial wastewater solution through adsorption process using adsorbent mixtures of ‘mahkota dewa’ (Phaleria marcocarpa (Scheff)) and clay or loam soil. The effects of high flow rate and packing were experimentally investigated. The adsorption material was made through drying and mixing. This mixture will be used in the process of adsorption by the column bed. The experimental results showed that the amount of chromium ions are absorbed increases with increasing contact time. Reducing the concentration of chromium ions rapidly occur at regular intervals up to 30-40 minutes. The variation of flow rate indicates that the packing height of 60 cm and a flow rate of 2.32 ml/s the concentration of chromium ions are absorbed by 89.5195%. Keywords: Adsorption, mahkota dewa, clay, chromium